Self-Control in the Function of Predicting Internalized and Externalized Violent Behavior - Vujović, Gorjana (Kriminalističke teme, 2021)
The importance of studying the concept of self-control, as one of the mechanisms of adaptation, is especially recognized in the field of controlling various forms of socially unacceptable behaviors, and thus violent behavior. The research was conducted with the aim to explore the predictive power of self-control in the context of internalized and externalized violent behavior. The sample was 385 final-grade high school students. As the measuring instruments, the self-control scale as well as the scale for examining the frequency of manifested internalized and externalized violent behavior have been used. Linear regression analysis has been applied. Results show that dimensions of self-control Healthy habits (β= -0.331), Deliberate (β= -0.183), Reliability (β= -0.130) and General capacity for self-discipline (β= -0.135) significantly predicts internalized violent behavior, dimensions Healthy habits (β= -0.285) and General capacity for self-discipline (β= -0.141) predicts externalized violent behavior. The importance of the concept of self-control for understanding behavior has been reaffirmed, by emphasizing the manifestation of internalized and externalized violent behavior.